2014
DOI: 10.1073/pnas.1411477111
|View full text |Cite
|
Sign up to set email alerts
|

Oil platforms off California are among the most productive marine fish habitats globally

Abstract: Secondary (i.e., heterotrophic or animal) production is a main pathway of energy flow through an ecosystem as it makes energy available to consumers, including humans. Its estimation can play a valuable role in the examination of linkages between ecosystem functions and services. We found that oil and gas platforms off the coast of California have the highest secondary fish production per unit area of seafloor of any marine habitat that has been studied, about an order of magnitude higher than fish communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
178
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(181 citation statements)
references
References 55 publications
3
178
0
Order By: Relevance
“…Claisse et al 2014, Friedlander et al 2014, Pradella et al 2014). While there is growing evidence to confirm that a variety of fish species aggregate around artificially installed hard structures in marine environments worldwide (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Claisse et al 2014, Friedlander et al 2014, Pradella et al 2014). While there is growing evidence to confirm that a variety of fish species aggregate around artificially installed hard structures in marine environments worldwide (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study by Love et al () found evidence that platforms were important for the larval production of bocaccio and cowcod, which would contribute to the recovery of these 2 overfished species. In addition, a more recent article, which was not available at the time of this study, highlights the substantial contribution (on a per unit basis) of California platforms to fish production (see Claisse et al ).…”
Section: Methodsmentioning
confidence: 90%
“…This is generally interpreted to mean the absence of all debris associated with oil and gas drilling, production, and transport operations, rather than re‐establishing the specific biological communities that existed before the platform's installation. However, in the time since most of these leases were signed, 1) technological advances have allowed for alternatives to full removal; and 2) studies have shown that the habitat on and under a platform has the potential to become more diverse and biologically productive than preplatform habitat (see Pondella et al this issue; Claisse et al ). As a result, laws and regulations have changed to allow for alternative uses ranging from aquaculture to alternative energy production to artificial reefs that enhance biological production or fishing opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the "rig to reef " approach is to use the decommissioned structures for fisheries yield and production, for recreational activities, to prevent trawling, to repair degraded marine habitats, and for overall economic and social benefit. Ultimately a reefbased food chain may develop providing food sources for larger organisms such as fish (e.g., Claisse et al, 2014). Such a rig-reef community may vary considerably from the naturally occurring species composition and also affect local nutrient recycling within the water column and settling of nutrients to the seafloor, thereby affecting benthic organisms surrounding the reef area.…”
Section: Decommissioningmentioning
confidence: 99%